A historical appraisal of ethics and civilization in Malaysia from pre-colonial to post-colonial era - Hamzani, Dayang Nurhazieqa; Amir Abdullah, Amini; Awang, Mohd. Daud; Abdul Kadir, Mohammad Nidzam; Mohd. Fadzil, Ahmad Faathin (Human Resource Management Academic Research Society, 2021)
This paper discusses the development of ethics and civilization with regards to Malaysia’s history from its pre-colonial to post-colonial times. This paper analyses the meaning of ethics in Ancient Greek and its relationship to civilization and how ethical framework has changed throughout particular civilizations. It also discusses how the religious ethical framework as well as local culture and customs in Malaysia were affected when Western modernity was introduced to this region. It is argued that both the Hindu-Buddhist period and the Muslim sultanates period have a similarity in their ethical framework in that both frameworks are informed by a belief in the divine, much like the Homeric period in Ancient Greece. On the discussion on the colonial period, this paper emphasizes and draws distinctions between the Portuguese, the Dutch and the British taking into consideration the main events that had happened in Europe between the Portuguese’ conquest of Malacca in 1511 and the British colonization in Malaya in 1824. Finally, this paper discusses on what this means to post-colonial Malaysia and the challenges it brings to the ethical discussion in Malaysia as well suggestions for possible meeting points to counter these challenges.